DIVE AND DECOMPRESSION SICKNESS - A REVIEW. (Fiep Bulletin - online, 2013)
Introduction: the objective of this study was to investigate the decompression sickness or Baropatias in various modalities of diving at the Brazilian coast, giving attention to the public health problem that affects fishermen, specifically those of lobsters, which utilize empirical ancestors teachings. Materials and methods: the method applied was an analytical type, having with database specific sites, articles, journals and books in an attempt to explain the phenomenon. Results: it was evidenced that the theme over the years haven't been getting the attention and much less debated the way it's been conducted. Conceives that the practice of diving, free from accidents, depends on the effectiveness, compliance with the technical requirements and their adaptation to the levels of development of individual prerequisites. Another highlight was that the dive modes are not analyzed in isolation, with no differences in this respect, and that in most studies, are only considered cases where the diver is empowered. Conclusion: The notes indicate that the incidence of decompression sickness is insignificant, about  1% of the divers enabled in the world are affected, however, there is a gap, which don't describes the number of cases concerning subsistence fishing.
Keywords: Decompression sickness; Baropatias; diving; lobster fishermen.